Analisis Perubahan Representasi Gender Dalam Iklan Televisi Di Indonesia - Arfian Suryasuciramdhan; Lapina Lena; Khansa Luqyana Meida; Yesya Vatria Barasa (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
Utilizing a qualitative descriptive methodology, this study investigates the Change in Gender Representation in Television Advertisements in Indonesia. The analysis we have conducted reveals how social constructions of gender are reflected and influenced by television advertisements through the semiotic lens of Roland Barthes. The results of this study indicate that gender representation in television advertisements has shifted from traditional stereotypes to more balanced and realistic roles, reflecting changes in the way society views gender. Advertisements serve not only as a communication tool but also influence societal understanding of gender equality. The findings suggest that mass media plays a significant role in shaping and conveying messages about gender. Thus, television advertisements can assist the audience in understanding gender roles in society in a more inclusive and autonomous manner.